2008
DOI: 10.1038/ng.253
|View full text |Cite
|
Sign up to set email alerts
|

Flowering-time genes modulate meristem determinacy and growth form in Arabidopsis thaliana

Abstract: Plants have evolved annual and perennial life forms as alternative strategies to adapt reproduction and survival to environmental constraints. In isolated situations, such as islands, woody perennials have evolved repeatedly from annual ancestors 1 . Although the molecular basis of the rapid evolution of insular woodiness is unknown, the molecular difference between perennials and annuals might be rather small, and a change between these life strategies might not require major genetic innovations 2,3 . Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
320
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(345 citation statements)
references
References 28 publications
(27 reference statements)
16
320
1
8
Order By: Relevance
“…QTLs for additional vegetative and reproductive traits map to this locus in multiple crosses Wills and Burke 2007;, and NILs segregating for the locus show genotype-dependent differences in some of these traits (Blackman et al 2010). Genetic evidence supports roles for FT in plant architecture, meristem size, leaf development, and abscission zone formation in Arabidopsis and tomato ( Jeong and Clark 2005;Jeong et al 2008;Melzer et al 2008;Shalit et al 2009;Krieger et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…QTLs for additional vegetative and reproductive traits map to this locus in multiple crosses Wills and Burke 2007;, and NILs segregating for the locus show genotype-dependent differences in some of these traits (Blackman et al 2010). Genetic evidence supports roles for FT in plant architecture, meristem size, leaf development, and abscission zone formation in Arabidopsis and tomato ( Jeong and Clark 2005;Jeong et al 2008;Melzer et al 2008;Shalit et al 2009;Krieger et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Evolution of woody taxa from herbaceous progenitors is well established (e.g., Bö hle et al 1996;Ballard and Sytsma 2000), and such a transformation may occur relatively rapidly with minimal genetic change (Thomas et al Groover 2005), such that the genetic distinction between H. winteri and H. annuus may be subtle. Molecular studies suggest that the development of woody characteristics may be linked to the timing of flowering (Melzer et al 2008;Lens et al 2012). Field observations of first-year plants of H. winteri and H. annuus reveal relatively few clear morphological differences; however, differences in vascular differentiation has been observed as early as three weeks postgermination (Moyers and Rieseberg 2013).…”
Section: Notes and Discussionmentioning
confidence: 99%
“…Previous studies in A. thaliana suggested that FT, which is a target of FLC, is involved in memory of 269 floral commitment (Melzer et al, 2008;Liu et al, 2014;Müller-Xing et al, 2014). Therefore, we 270 compared the expression of the A. alpina FT homolog, AaFT1 (Adrian et al, 2010), in shoot apices 271 after different periods of vernalization.…”
Section: E G and I) 221mentioning
confidence: 99%